Autism spectrum disorder in children born preterm—role of exposure to perinatal inflammation - Meldrum, Suzanne J.; Strunk, Tobias; Currie, Andrew; Prescott, Susan L.; Simmer, Karen; Whitehouse, Andrew J. (Frontiers in Neuroscience, 2013)
Autism Spectrum Disorder (ASD) is the collective term for neurodevelopmental disorders characterised by qualitative impairments in social interaction and communication, and a restricted range of activities and interests. Many countries, including Australia, have reported a dramatic increase in the number of diagnoses over the past three decades, and recent reports suggest a prevalence of ASD of 1 in every 110 individuals (~1%). The potential role for an immune-mediated mechanism in ASD has been implicated by several studies, and some evidence suggests a potential link between prenatal infection-driven inflammation and subsequent development of ASD. Furthermore, contemporary studies have reported a markedly increased prevalence of ASD in children born preterm, who are at highest risk of exposure to perinatal inflammation. However, the mechanisms that underpin the susceptibility to infection-driven inflammation during pregnancy and risk of preterm birth, and how these intersect with the subsequent development of ASD in the offspring, is not understood. This review aims to summarise and evaluate the potential mechanisms and evidence for the role of prenatal infection on the central nervous system, and how it may increase the susceptibility for ASD pathogenesis in children born preterm.